WAIST CIRCUMFERENCE AS INDICATOR COMPONENTS OF METABOLIC SYNDROME IN THE SIBERIAN POPULATION - G. I. Simonova (Bûlleten' Sibirskoj Mediciny, 2014)
Object of research: to determine the cut-off point of waist circumference (WC) identify the components of metabolic syndrome (MS) in a large industrial center of Western Siberia.In the period from 2003 to 2005 in the screening population surveyed 9362 people, including 4268 men (45.6%) and 5094 women (54.4%).The response rate was 61%. The study protocol included a sociodemographic data, measurement of blood pressure (BP), anthropometry (height, weight, WC), the definition of biochemical parameters. Statistical analysis was performed using the package SPSS. To determine the cut-off points of the used ROC model.In the group with ≥2 components of MS cut-off point WC from the men was 93.3 cm (sensitivity 72%, specificity 83%), women – 90.2 cm (sensitivity 72%, specificity 62%).The lowest cut-off point WC marked BP ≥ 130/85 mm Hg for men – 90 cm (sensitivity 66.8%, specificity 58.1%), for women – 86.5 cm (sensitivity 71.0%, specificity 55.7%). The highest cut-off point from the defined patients with diabetes for men was 99.0 cm (sensitivity 61%, specificity 70.2%), for women – cm (sensitivity 64.1%, specificity 65.9%).Conclusions: Cut-off point from the persons with the presence of ≥2 MS components in Siberian population 45–69 years, in accordance with the ROC analysis are 93.3 cm for men and 90.2 cm for women. The lowest cut-off point WC marked BP ≥ 130/85 mm Hg for men – 90 cm, for women – 86.5 cm. The highest cut-off point from the defined patients with diabetes for men was 99.0 cm, for women – 95 cm.